Rethinking Tibetan Buddhism in Post-Mao China, 1980–2015 - Caple, Jane E. (Review of Religion and Chinese Society, 2020)
The literature on Tibetan Buddhism in post-Mao China presents a bifurcated history: ethnic nationalism and (traditional) identity are foregrounded in scholarship on the revitalization of Tibetan Buddhism in Tibet; consumption and/or (global) modernism are emphasized in studies of its spread in Sinophone China. Although there are considerable historical and social differences between these different constituencies, these characterizations do not fully capture the social differences, as well as convergences, that have shaped everyday engagements with Tibetan Buddhism among Tibetans and Chinese. Drawing on ethnographic data collected in northeastern Tibet and other recent ethnographic studies, I attempt to complicate this picture, arguing that we need to pay greater attention to the affective dimension of Chinese engagements, the social embeddedness of Tibetan Buddhist institutions in the Tibetan context, and the transformations that have taken place in Tibetan areas, as elsewhere in China.